Magnetic behaviour of (Fe2O3)x (TeO2)1-x glass system. - Alassan, Zarifah; Mohamed Kamari, Halimah; Hashim, Mansor; Zakaria, Azmi; Wan Yusoff, Wan Mohamad Daud (National Institute of Materials Physics, National Institute of Optoelectronics, 2010)
Homogeneous (Fe2O3)x (TeO2)1-x were synthesis using melt- quenching technique for x= 0.1-0.3 in the interval of 0.05. The binary glasses were dark brown in colour. The amorphous structure of glasses was confirmed by the X-ray diffraction spectrum. The physical properties such as density and molar volume have been determined in room temperature and were found decrease with Fe2O3 contents increase. From the vibrating-sample magnetometer (VSM) measurement it was observed that that magnetization of glass increase almost linearly with applied fields and shows paramagnetic materials behavior.